2021
DOI: 10.1111/jcmm.16581
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental effect of iron on OA chondrocytes: Importance of pro‐inflammatory cytokines induced iron influx and oxidative stress

Abstract: Iron overload is common in elderly people which is implicated in the disease progression of osteoarthritis (OA), however, how iron homeostasis is regulated during the onset and progression of OA and how it contributes to the pathological transition of articular chondrocytes remain unknown. In the present study, we developed an in vitro approach to investigate the roles of iron homeostasis and iron overload mediated oxidative stress in chondrocytes under an inflammatory environment. We found that pro‐inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Another study by Jing et al revealed that excess iron-mediated mitochondrial dysfunction in chondrocytes had a close association with oxidative stress. The association was established via the process of ROS generation, which in turn promoted the expression of OA-related catabolic markers (Jing et al, 2021a). The iron chelation method further confirmed the vital role of iron in chondrocyte dysfunction.…”
Section: Effects Of Iron Overload On Chondrocyte Dysfunction and Cart...mentioning
confidence: 72%
See 2 more Smart Citations
“…Another study by Jing et al revealed that excess iron-mediated mitochondrial dysfunction in chondrocytes had a close association with oxidative stress. The association was established via the process of ROS generation, which in turn promoted the expression of OA-related catabolic markers (Jing et al, 2021a). The iron chelation method further confirmed the vital role of iron in chondrocyte dysfunction.…”
Section: Effects Of Iron Overload On Chondrocyte Dysfunction and Cart...mentioning
confidence: 72%
“…Multiple independent clinical studies have been conducted, and the results have indicated that elderly patients with high ferritin content have a four-fold increased risk of suffering from OA than patients with low ferritin content in their bodies. It has also been observed that the ferritin content has a positive association with the severity of joint through imaging analyses (Park et al, 2012;Jing et al, 2021a;Ke et al, 2021). Moreover, studies indicated that the incidence of high iron storage was higher in the elderly compared with populations of other ages, and this transition was more pronounced in older women than in men (Chen et al, 2015).…”
Section: Aging-and Estrogen Deficiency-induced Osteoarthritismentioning
confidence: 97%
See 1 more Smart Citation
“…Excessive iron also can produce reactive oxygen species through Fenton or Haber Weiss reaction, resulting in oxidative stress ( 69 ). This will over activate matrix metalloproteinases that degrade extracellular matrix, thereby reducing the resistance of cartilage to mechanical stress and exacerbating OA ( 70 ).…”
Section: Impact Of Eight Trace Elements On Oamentioning
confidence: 99%
“…Cartilage degeneration brought with reduced expression of transcripts for aggrecan and type II collagen in iron overload animals ( 112 ). The cartilage injury caused by systemic iron overload is also related to the increased transcriptional counts of pro-inflammatory cytokines such as interleukin-1β and tumor necrosis factor-α in the cartilage and infrapatellar fat pad ( 70 ). Iron overload can destroy the metabolism of chondrocytes and promote the establishment of an OA-related phenotype ( 112 ).…”
Section: Impact Of Eight Trace Elements On Oamentioning
confidence: 99%